الانتقال الديمقراطي بين التوجهات السياسية والمتطلبات السوسيو-اقتصادية دراسة حالة الجزائر - مسعودي, يونس (جامعة الوادي University of Eloued, 2019)
يحاول الباحث في هذا المقال إبراز مفهوم الانتقال الديمقراطي من جهة، ومكانة هذا المفهوم كممارسة في الجزائر من جهة أخرى، إلى جانب التركيز على تموقع هذا المفهوم ما بين التوجهات السياسية المتمثلة أساسا في فهم مشكلات الدولة وتحقيق متغيرات الأمن والاستقرار السياسي وانتقال السلطة؛ وبين المتطلبات السوسيو-اقتصادية والمتمثلة هي الأخرى في تحقيق النمو الاقتصادي (ثراء الدولة) وتجاوز أزمة توزيع الدخل وتوفير التعليم. Through this article, the researcher tries to spotlight democratic transition as a concept in theory and to highlight its status as a practice in Algeria. The focus is also put on the positioning of this concept in the course of both political trends, i.e. understanding the State problems and achieving the variables of security, political stability and the Power transfer, and the socio-economic requirements, i.e. achieving the economic growth (State wealth), overcoming the crisis of income distribution and providing education, as well.
Keywords: الانتقال الديمقراطي – التنمية السياسية – التنمية الاجتماعية - التنمية الاقتصادية – الاستقرار السياسي – انتقال السلطة – النمو الاقتصادي- الجزائر; Democratic Transition – Political Development – Social Development – Economic Development – Political Stability – Transfer Of Power – Economic Growth – Algeria